Mitigating ICI at cell edges in cognitive-femtocell networks through fractional frequency reuse. (2016) - Ghosh, Joydev; Roy, Sanjay Dhar
In this paper, we consider a situation where femtocells are deployed over the existing macrocell network and share the same frequency spectrum with macrocells where we focus only on downlink situation. It is essential to implant femtocell at cell edges due to the fact that the number of outage user is large because of their position which is far away from macrocell base station (MBS) located at macrocell centre, more precisely at (0, 0) coordinates. In general, the uncoordinated deployment of femtocell creates the potential for severe interference to co-located femtocells, especially in dense deployment, resulting in large inter cell interference (ICI) effect on the users located at cell edges. Here, we propose dynamic FFR algorithm at cell edges to overcome all possible difficulties in the networks. Frequency reuse is an approach to increase the signal to interference plus noise ratio (SINR) and channel capacity (Bits/s/Hz). The bit error rate (BER) is also evaluated by maximal ratio combining (MRC) diversity technique for accurate transmission over multipath fading dispersive channels. The simulation results conclusively validate the superior performance of the network model in interference mitigation, precisely in high density FAP scenarios.